Tanggung Jawab Orang Tua dalam Mendidik Anak Menurut Alquran (Analisis terhadap Tafsir Al-Maraghi) - Azis, Abdul; Sa’adah, Enok Hilmatus (Jurnal Penelitian Pendidikan Islam, 2018)
This study aims to describe the role of parents in educating their early children according to the Quranic Al-Nisa letter verse 9 based on the interpretation of al-Maraghi. The method used in this study is library research, the primary data obtained from al-Maraghi interpretations that contain the thoughts of al-Maraghi priests. Data analysis follows the following stages: data processing, data categorization, data interpretation. This study yielded several findings. First, the Al-Nisa letter of verse 9 contains a warning to every parent to feel anxious and fearful when in the future they must leave their children in a weak and helpless state. Second, parents are responsible for educating their children at an early age. The educational aspects of parental responsibility include physical and spiritual education, faith education, and character education.